Optimizing structure of baffles on thermal performance of spiral solar air heaters. (August 2021) - Jia, Binguang; Yang, Luopeng; Zhang, Linhua; Liu, Bing; Liu, Fang; Li, Xiao
Highlights: The baffle structure effect on the microscopic characteristics of flow and heat transfer was numerically analyzed. Depressing the vortex played a key role in improving thermal performance of the SSAHs. The optimal structure of baffles with right angle and rectangular holes at turnings was proposed. Abstract: In order to further improve the thermal performance of spiral solar air heaters (SSAHs), three-dimensional mathematical models of four proposed types of spiral solar air heaters, including right angle spiral solar air heaters (RA-SSAHs), arc spiral solar air heaters (ARC-SSAHs), arc spiral solar air heaters with rectangular holes (ARC-RH-SSAHs) and rectangular holes spiral solar air heaters (RH-SSAHs), were developed by CFD to analyze the effect of baffles structure on the microscopic characteristics of flow and heat transfer. The profiles of velocity proved that the channel with both right angle turnings and rectangular holes contributed to decreasing the pressure loss by depressing the intensity and scale of the separated vortex and corner vortex. RH-SSAHs, which exhibited the highest collection efficiency among the four types of SSAHs, proved that the optimizing structure of baffles in channels contributed to reducing the heat loss rate by transparent cover plate more significantly than reducing the absorbed heat rate of air by increasing the transverse velocity and decelerating the air flowing along the channels due to bypass air through the holes.